2020
DOI: 10.1136/bmjgh-2020-002640
|View full text |Cite
|
Sign up to set email alerts
|

Availability and affordability of medicines and cardiovascular outcomes in 21 high-income, middle-income and low-income countries

Abstract: ObjectivesWe aimed to examine the relationship between access to medicine for cardiovascular disease (CVD) and major adverse cardiovascular events (MACEs) among people at high risk of CVD in high-income countries (HICs), upper and lower middle-income countries (UMICs, LMICs) and low-income countries (LICs) participating in the Prospective Urban Rural Epidemiology (PURE) study.MethodsWe defined high CVD risk as the presence of any of the following: hypertension, coronary artery disease, stroke, smoker, diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 22 publications
1
53
0
3
Order By: Relevance
“…MMM19 showed a slight decrease in the proportion of participants on antihypertensive medication, which could be a chance phenomenon since this is not a randomly selected general population sample or could be related to low medication availability as has been recently reported by the PURE study. 7 This study included 163 466 participants from low-, middle-, and high-income countries and showed that low availability of antihypertensive drugs is associated not only with lower levels of BP control but also with a higher risk of major cardiovascular events and mortality. 7 The communities with the lowest availability of drugs had the lowest education levels and the highest poverty rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMM19 showed a slight decrease in the proportion of participants on antihypertensive medication, which could be a chance phenomenon since this is not a randomly selected general population sample or could be related to low medication availability as has been recently reported by the PURE study. 7 This study included 163 466 participants from low-, middle-, and high-income countries and showed that low availability of antihypertensive drugs is associated not only with lower levels of BP control but also with a higher risk of major cardiovascular events and mortality. 7 The communities with the lowest availability of drugs had the lowest education levels and the highest poverty rates.…”
Section: Discussionmentioning
confidence: 99%
“… 7 This study included 163 466 participants from low-, middle-, and high-income countries and showed that low availability of antihypertensive drugs is associated not only with lower levels of BP control but also with a higher risk of major cardiovascular events and mortality. 7 The communities with the lowest availability of drugs had the lowest education levels and the highest poverty rates. 8 Therefore, these data reveal that in low- and middle-income countries like Colombia, low levels of hypertension control can be related to doctors’ inertia and patients’ poor adherence but also to high levels of inequality.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest paid government worker would need 2.6 days wages to pay for a 1 month supply of statins if bought from a public sector pharmacy, and 13.7 day wages if brought from a retail pharmacy (21). Lower availability and affordability of essential CVD meds have been associated with higher risk of major adverse cardiovascular events and mortality (HR 1.25, 95% CI 1.08 to 1.50) (22).…”
Section: Discussionmentioning
confidence: 99%
“…The Prospective Urban Rural Epidemiology (PURE) study has shown that preventive medications including aspirin, β blockers, angiotensin-converting enzyme inhibitors, and statins are unavailable and unaffordable for a large proportion of communities and households in low-income countries [ 13 ], and that lower availability and affordability of such essential CVD medications are associated with higher risk of major adverse cardiovascular events and mortality [ 14 ]. To curb the rising burden of CVD in sub-Saharan Africa, governments and health organizations should devote special efforts to scaling up access to essential CVD medications using key interventions such as differential pricing, bulk purchasing, and use of low-cost generics.…”
Section: Editorialmentioning
confidence: 99%